2014
DOI: 10.1007/s11250-014-0596-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing milk and fertility performances using selection index developed for Indian Murrah buffaloes

Abstract: Selection for genetically superior Murrah buffaloes under Network Project on Buffalo Improvement, India, is presently based on milk yield, and it was observed that even in the absence of any direct selection pressure applied on fertility, there has been a downward trend in fertility associated with the selection for milk yield. The aim of the study was to develop selection indices which include fertility besides milk yield in Murrah buffaloes. Data pertaining to 1,224 lactation records spread over a period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 7 publications
1
11
2
Order By: Relevance
“…(1991) and Valsalan et al. (2014) reported that an increase and decrease in economic values of traits even up to 25% and 50% causes no major change in the index coefficients and accuracy of indices.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…(1991) and Valsalan et al. (2014) reported that an increase and decrease in economic values of traits even up to 25% and 50% causes no major change in the index coefficients and accuracy of indices.…”
Section: Discussionmentioning
confidence: 98%
“…Valsalan et al. (2014) reported average expenditure per day per Murrah buffalo by considering the same items of expenditure as Rs. 216.12.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 13 buffalo breeds used for milk production in the country, the Murrah breed is the most important for dairy (Valsalan et al, 2014) and is the breed of choice for upgrading buffaloes for milk production . A National dairy plan implemented since 2011 aims to develop more productive animals (both cattle and buffaloes) and to develop and expand production systems to increase milk supply in India over a 15 year horizon (NDDB, 2014).…”
Section: Systems Of Dairy Production and The Main Dairy Genotypesmentioning
confidence: 99%
“…The first lactation length (FLL) in Murrah buffaloes ranged from 278.26 ± 3.19 days [28] to 373.10 ± 5.80 days [9]. Valsalan et al [29] reported lactation length 286.06 ± 1.72 days in Murrah buffaloes. The effect of season of calving on FLL reported significant [16] and non-significant [18,19,20,30,23].…”
Section: First Lactation Lengthmentioning
confidence: 99%